1984
DOI: 10.1111/1467-9566.ep10777358
|View full text |Cite
|
Sign up to set email alerts
|

The image of health: variations in perception by social class in a French population

Abstract: In order to determine how a population defines the meaning of health, a study was made using a sample of 4,000 respondents from Lorraine, in the north-eastern part of France. The respondents, all of whom were undergoing a health examination, were asked to respond to an open-ended question on what health meant to them. A total of 6,172 replies were obtained whose contents were classified into 41 main themes themselves regrouped under 10 heading (or groups of themes). The responses were cleady linked to the soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 8 publications
3
51
0
1
Order By: Relevance
“…This definition of wellness focuses on the absence of (physical) problems rather than on any positive abilities or characteristics, and as such is a lay version of a biomedical definition of health. This theme was documented in early large-scale qualitative work carried out in France (d 'Houtaud & Field, 1984, 1986 which suggested that such ideas were more common in people aged over 50 and in manual workers. Williams also describes the absence of illness account in his research with Scottish participants aged 60 and over living in 'working class' areas (Williams, 1983).…”
Section: /11/08mentioning
confidence: 93%
“…This definition of wellness focuses on the absence of (physical) problems rather than on any positive abilities or characteristics, and as such is a lay version of a biomedical definition of health. This theme was documented in early large-scale qualitative work carried out in France (d 'Houtaud & Field, 1984, 1986 which suggested that such ideas were more common in people aged over 50 and in manual workers. Williams also describes the absence of illness account in his research with Scottish participants aged 60 and over living in 'working class' areas (Williams, 1983).…”
Section: /11/08mentioning
confidence: 93%
“…In this respect, perhaps the first and most obvious area of application concerns the fact that these differing social class orientations towards the body are evident in lay concepts of health and illness (Blaxter and Patterson 1982, Blaxter 1983, Crawford 1984, d'Houtaud and Field 1984, Pill and Stott 1985, Calnan 1987, Blaxter 1990, Stainton-Rogers 1991, Saltonstall 1993, Thus in d' Houtaud and Field's (1984) study of a French population's views of health, for instance, it was found that, for members of the privileged classes, health is appropriated by the individual and employed in a hedonistic way through the expressive use of the body (i.e. seen in abstract terms), whereas the health of working-class people, in contrast, is utilised for the benefit of society (i.e.…”
Section: The Body Class and Lifestyles: Health And The Search For DImentioning
confidence: 99%
“…When researchers speak of health beliefs they usually refer to a niunber of issues: how people in general regard health matters as compared with medical practitioners (Blumhagen, 1980); how ordinary people give lay accounts of their experiences of ill-health during their lifetime (Blaxter 1983, Williams 1990), how they think about avoiding disease (Herzlich 1973, Pill andStott 1982) how they define health (Baumann 1961, Blaxter 1990 or how people in different sections of society hold different views about health matters (Blair 1993, Calnan 1987, d'Houtaud and Field 1984, Pierret 1993.…”
Section: Introductionmentioning
confidence: 99%